Manipulation of heart rate variability can modify response to anger-inducing stimuli. (2nd September 2016) - Francis, Heather M.; Penglis, Kathryn M.; McDonald, Skye
ABSTRACT: Research suggests that heart rate variability (HRV) is a physiological indicator of the flexibility of the autonomic nervous system and can provide an objective measure of an individual's ability to appropriately match emotional responses to environmental demands. The present study investigated whether angry response to emotional stimuli was related to HRV, and whether manipulation of HRV using biofeedback could change the anger response in a healthy adult population. Fifty-eight participants received HRV biofeedback ( n = 29) or an active control condition ( n = 29). HRV measures included standard deviation of normal-to-normal intervals (SDNN), low-frequency (LF) and high-frequency (HF) power, and was recorded across three sessions: baseline, training, and anger induction. The anger induction procedure resulted in increased subjective experience of anger, as well as physiological changes. The biofeedback group had higher HRV than active controls both during the training session (SDNN and LF HRV) and during anger induction (LF HRV). HRV during anger induction was significantly associated with self-reported emotional response for participants receiving biofeedback but not for active controls. Results provide support for HRV as an index of emotion regulation, specifically anger. Further research is needed to determine whether long-term HRV biofeedback can have a lasting effect on managing anger.